Assessment of ecological resilience and its response mechanism to land spatial structure conflicts in China’s Southeast Coastal Areas - Yuemin Fan; Guoen Wei (Ecological Indicators)
As a key region in China’s reform and opening up, the China’s Southeast Coastal Areas (CSCA) is experiencing a rapid decline in ecological resilience and environmental risk resistance due to accelerated socioeconomic development. Consequently, assessing the impact of land spatial structural transformation on environmental resilience and developing suitable regulatory strategies has emerged as a critical issue in this region. This study develops an assessment framework for ecological resilience (ER) and “Production-Living- Ecological” space structure conflict (SCCI) utilizing multi-source remote sensing data and socioeconomic statistics from 2000 to 2022. This framework aims to uncover long-term evolution patterns, spatial correlations, and driving mechanisms. The study finds that the ER of CSCA has exhibited a convergence trend of 11.55% since the 21st century, whereas the “Production-Living- Ecological” space structure conflict achieved an overall increase of 6.34%. The spatial mismatch between ER and SCCI is the primary clustering type of their geographical association. However, the proportion of cities exhibiting this mismatch is gradually decreasing, primarily concentrated in coastal urban agglomerations and southeastern hilly regions. An increase of 1 unit in SCCI results in a decrease in local ecological resilience by 0.130–0.207, while neighboring areas experience a decline in environmental resilience of 1.764–3.849. This indicates that the spatial externality effects of spatial structural conflict on ecological resilience are significantly greater than the local effects. Furthermore, spatial complexity, instability, and vulnerability exacerbate the negative impact on ecological resilience through nonlinear interactions. This finding supports the feasibility of implementing “Production-Living-Ecological” space control mechanisms—scale transformation, stability maintenance, and connectivity building—to restore ecological resilience. Addressing these issues offers new insights into the relationship between spatial transformation and ecological resilience in the region. It provides valuable lessons for the territorial spatial control planning aimed at enhancing ecological resilience.